The Efficacy and Medium to Long-Term Follow-Up of Transcatheter Retrograde Closure of Perimembranous Ventricular Septal Defects via the Femoral Artery With Amplatzer Duct Occluder II in Children - Jiang, Diandong; Zhang, Jianjun; Fan, Youfei; Han, Bo; Zhao, Lijian; Yi, Yingchun; Lv, Jianli; Wang, Jing (Frontiers in Pediatrics, 2021)
Objective: The aim of this study was to assess the efficacy and safety of transcatheter retrograde closure of perimembranous ventricular septal defect (pmVSD) via the femoral artery with an Amplatzer Duct Occluder II (ADO II) in children. Methods: The clinical and follow-up data of 102 children who had successfully undergone transcatheter retrograde closure of pmVSD via the femoral artery with Amplatzer Duct Occluder II (ADO II) from February 2012 to June 2019 in our centre were retrospectively reviewed. Results: In 102 of 103 patients, the defects were successfully closed (99.0%). The average age was 4.03±1.84 years and the mean weight was 17.50±5.58 kg. The mean diameter of the defects was 2.58±0.63 mm. 100 of the occluders had a waist length of 4 mm. The complete closure rate was 89.2% 24 hours after the procedure and 98% at the last follow-up. The follow-up period ranged from 6 to 92 months, with a median of 36 months. One child developed new mild aortic regurgitation (AR), and 9 patients developed new mild tricuspid regurgitation (TR). During follow-up, TR disappeared in 5 patients and decreased in 4 patients, and AR relieved in one patient. One patient developed intermittent complete left bundle branch block 4 days after the procedure and recovered sinus rhythm 2 days later. No serious complications occurred. Conclusion: Transcatheter retrograde closure of pmVSD via the femoral artery with ADO II in children is safe, feasible and effective in selected patients.